Ubrogepant: An Oral Calcitonin Gene-Related Peptide (CGRP) Receptor Antagonist for Abortive Migraine Treatment. Issue 3 (March 2022) - Nedd, Madell; Garland, Scott; Falk, Nathan; Wilk, Ashley
Objective: To review the pharmacology, efficacy, and safety of ubrogepant as an abortive migraine treatment. Data Sources: A literature search of MEDLINE and PubMed was performed (January 2006 through May 2021) using the following search terms: ubrogepant, calcitonin gene related peptide, and abortive migraine therapy . Study Selection and Data Extraction: Relevant studies evaluating ubrogepant's pharmacology, efficacy, and safety in humans for the treatment of migraine were considered Data Synthesis: Ubrogepant is a calcitonin gene-related peptide receptor antagonist approved by the Food and Drug Administration for the acute treatment of migraine via data from ACHIEVE I and II. From ACHIEVE I, ubrogepant demonstrated superiority to placebo in freedom from migraine pain at 2 hours postdose (50-mg dose: odds ratio [OR] = 1.83, 95% CI = 1.25-2.66; 100-mg dose: OR = 2.04, 95% CI = 1.41-2.95) and freedom from most bothersome symptom (MBS; 50-mg dose: OR = 1.70, 95% CI = 1.27-2.28; 100-mg dose: OR = 1.63, 95% CI = 1.22-2.17). ACHIEVE II trial demonstrated efficacy of ubrogepant 50 mg compared with placebo (2-hour pain freedom: OR = 1.62, 95% CI = 1.14-2.29; 2-hour MBS freedom: OR = 1.65, 95% CI = 1.25-2.20). Relevance to Patient Care and Clinical Practice: Ubrogepant is a viable option for patients who are unable to tolerate nonsteroidal anti-inflammatory drug or triptan therapy because of ineffective relief or contraindications that limit use. Conclusions: Ubrogepant is a well-tolerated effective abortive migraine treatment that bridges a gap in therapy for many patients who previously could not tolerate other first-line treatments.